Survey of Safety Culture and Its Relation to Work-Related Accidents in a City Train Project - Hamidreza NAJMABADI; Gholamhossein HALVANI; Alireza ESMAEILI; Hamideh MIHANPOUR (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: More than 85% of accidents are due to unsafety working and causes of 85 to 98% of occupational accidents are perspectives, behavior and culture. Therefore, the purpose of this study is to survey of safety culture and its relation with work-related accidents in an urban train project. Methods: This study was conducted on 180 workers. To collect data, were used a standard safety culture questionnaire that contains 62 questions related to 5 areas of education, work environment, priority to safety, information exchange and commitment management. Data were analyzed by SPSS-20 software. Results: The overall average of safety culture score in the urban train was 2,420, which is a positive project culture. Among the different dimensions of the safety culture, the lowest mean safety culture score was related to the work environment dimension (58.5%) and the highest average was priority to safety (84%). The most common cause of accidents was surface damage (66.6%). There was a significant relationship between safety culture with age groups and job satisfaction (P <0.05). Conclusion: According to the results, prioritizing safety at work and education has been one of the most important factors in achieving a high score on the safety culture of the project. On the other hand, due to the type of work activity, the work environment has been considered as the main factor in reducing the safety culture score. The most important thing in preventing minor accidents has arisen and promotion of safety culture, observing 5s in the workplace.